Fundamentals of electromagnetic theory - Dash, Saroj K (PHI learning, 2011)
Fundamentals of electromagnetic theory / Dash, Saroj K.. -- New Delhi: PHI learning, 2011 539.2 D229e2 2nd en. No. of Copies : 1